ENO3 Inhibits Growth and Metastasis of Hepatocellular Carcinoma via Wnt/β-Catenin Signaling Pathway - Cui, Honglei; Guo, Danfeng; Zhang, Xiaodan; Zhu, Yaohua; Wang, Zhihui; Jin, Yang; Guo, Wenzhi; Zhang, Shuijun (Frontiers in Cell and Developmental Biology, 2021)
β-enolase (ENO3) is a metalloenzyme that functions during glycolysis and has been revealed ectopic expression in different cancers. However, the function and underlying modulatory mechanisms of ENO3 in hepatocellular carcinoma (HCC) are still elusive. Here, we discovered that ENO3 was remarkably down-regulated in human HCC tissue in contrast to those in noncancerous tissue. Moreover, low expression of ENO3 was related to the poor prognosis of HCC patients. Overexpression of ENO3 suppressed proliferative, migratory, and invasive abilities of HCC cells both in vitro and in vivo, whereas knocking down ENO3 led to the opposite effect. In addition, we revealed that ENO3 repressed the epithelial-mesenchymal transition (EMT) process with its biomarker variations. Mechanistic research unveiled that ENO3 suppressed the Wnt/β-catenin signal, which subsequently modulated the transcription of its target genes associated with the proliferation and metastasis capacity of HCC cells. Taken together, our study uncovered that ENO3 acted as a tumor inhibitor in HCC development and implied ENO3 as a promising candidate for HCC treatment.